Productivity dynamics in emerging and industrialized countries - Das, Deb Kusum (London Routledge, 2018)
The world, of late, has seen a productivity slowdown. Many countries continue to recover from various shocks in the macro business environment, along with structural changes and inward-looking policies. In contemporary times of growth slumps, various exits and protectionist regimes, this book engages with the study of productivity dynamics in the emerging and industrialized economies. The essays address the crucial aspects, such as the roles of human capital, investment accounting and datasets, that help to understand of productivity performance of global economy and its several regions.
Keywords: v